Centrality dependence of the nuclear modification factor of charged pions, kaons, and protons in Pb-Pb collisions at √sNN=2.76 TeV - Adam, Jaroslav; Angelov, Venelin; Bock, Friederike; Busch, Oliver; Deisting, Alexander; Fleck, Martin; Glässel, Peter; Karayan, Lilit; Klein, Jochen; Knichel, Michael Linus; Leardini, Lucia; Mercado Pérez, Jorge; et al. (Physical review, 2016)
Transverse momentum (pT) spectra of pions, kaons, and protons up to pT=20GeV/c have been measured in Pb-Pb collisions at √sNN=2.76TeV using the ALICE detector for six different centrality classes covering 0%-80%. The proton-to-pion and the kaon-to-pion ratios both show a distinct peak at pT≈3GeV/c in central Pb-Pb collisions that decreases for more peripheral collisions. For pT>10GeV/c, the nuclear modification factor is found to be the same for all three particle species in each centrality interval within systematic uncertainties of 10%-20%. This suggests there is no direct interplay between the energy loss in the medium and the particle species composition in the hard core of the quenched jet. For pT<10GeV/c, the data provide important constraints for models aimed at describing the transition from soft to hard physics.
Im Titel stehen der Ausdruck "sNN" unter dem Wurzelsymbol
Gesehen am 28.07.2020
ALICE collaboration: J. Adam, V. Anguelov, F. Bock, O. Busch, A. Deisting, M.G. Fleck, P. Glässel, L. Karayan, J. Klein, M.L. Knichel, L. Leardini, J. Mercado Pérez, H. Oeschler, K. Oyama, Y. Pachmayer, F. Reidt, K. Reygers, R. Schicker, J. Stachel, J.H. Stiller, M.A. Völkl, Y. Wang, J. Wilkinson, B. Windelband, M. Winn, A. Zimmermann [und 963 weitere]